Sex-Specific Sub-Acute Toxicity and Immunomodulatory Profile of a Nigerian Polyherbal Supplement (Napherbs) In Albino Wistar Rats (Nigerian Journal of Physiological Sciences, 2025)
NaPherbs, a Nigerian-based polyherbal supplement compounded with Moringa oleifera, Vernonia amygdalina, Garcinia kola, etc. is consumed locally as an immune-boosting nutraceutical. In this study, we investigated its preliminary immune-boosting mechanisms and sub-acute toxicity profile in both male and female albino Wistar rats. A total of 40 Wistar rats (20 males and 20 females) were randomly allotted to 5 experimental groups (n=8, 4 males and 4 females); control, 125, 250, 500 and 1000 mg/kg/day of NaPherbs for 30 consecutive days. The animals were anesthetized, and cardiac puncture was used to obtain serum for biochemical assays such as the serum lipid profile, immunoglobulins concentration, proinflammatory cytokines’ concentration and liver function enzymes; and whole blood for hematological assessment. In vivo antioxidant assays were carried out also on the liver homogenates, while the liver and kidneys were examined histologically in both male and female animals. There was a dose-dependent increase in the neutrophil: leucocyte ratio in the female animals. This has been linked to physiological stress, underlying disease condition and most recently a risk factor for early onset chronic kidney disease (CKD). NaPherbs did not pose any major cardiovascular risk across the groups, and there seemed to be some level of cardioprotection judging from the reduction in low-density lipoprotein cholesterol (LDL-c), triglyceride (TG) and total cholesterol (TC) observed in both sexes. The antioxidant indices assayed for were not significantly (P